2013
DOI: 10.1021/bi401126z
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Bohr Effects: Atomic Origin of the Histidine Residue Contributions

Abstract: The Bohr effect in hemoglobin, which refers to the dependence of the oxygen affinity on the pH, plays an important role in its cooperativity and physiological function. The dominant contribution to the Bohr effect arises from the difference in the pKa values of His residues of the unliganded (deoxy) and liganded (carbonmonoxy) structures. Using recent high resolution structures, the residue pKa values corresponding to the two structures are calculated. The method is based on determining the electrostatic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 55 publications
2
34
0
2
Order By: Relevance
“…Tables 4 and 5 (taken from Tables 4 and 5 of ref. 110 ) give both their calculated and our experimentally determined values. Structures, 2DN2 (for deoxy) and 2DN3 (for oxy), with the highest resolution, were used in most of their analyses.…”
Section: Functionmentioning
confidence: 92%
See 1 more Smart Citation
“…Tables 4 and 5 (taken from Tables 4 and 5 of ref. 110 ) give both their calculated and our experimentally determined values. Structures, 2DN2 (for deoxy) and 2DN3 (for oxy), with the highest resolution, were used in most of their analyses.…”
Section: Functionmentioning
confidence: 92%
“…110 Their calculated pK values for the N-terminal α1Val are 8.60 and 7.80 for deoxy- and oxy-Hb A, respectively. They found that the number of hydrogen ions released from the two α-chains at pH 8.4 is 0.32, corresponding to 16% of the Bohr effect at that pH.…”
Section: Functionmentioning
confidence: 98%
“…Following Zheng et al, the atomic coordinates were taken from the high resolution (1.25 Å) X‐ray structures of the deoxy (PDB 2DN2) and oxy forms (PDB 2DN3) . The deoxy form was crystallized at T = 298 K, pH = 6.5 with ammonium sulfate and ammonium phosphate, and is thought to provide a good representation of the solution structure. The oxy form was crystallized at T = 100 K, pH = 6.7, with sodium phosphate, potassium phosphate and glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we have tested the method on a much larger set of acid/base constants, 149 instead of 78 previously. One of the proteins was hemoglobin, for which we also computed the Bohr effect: the number of protons that bind when the protein switches from its deoxy to its oxy form, which is of physiological interest . The FDB performance was slightly but systematically better than NEA, with an rms deviation between the computed and experimental p K a 's of 1.04 instead of 1.16 with NEA, a higher correlation with experiment, fewer large errors, and an improved Bohr effect.…”
Section: Introductionmentioning
confidence: 99%
“…9 Hemoglobin molekülü, tetramer yapıda olup; hem ve globin proteinlerinin bir araya gelmesi ile oluşur. Hem oksijene bağlanma özelliğine sahip Fe +2 (ferröz demir) ve protoporfirin IX halkasından oluşur 10 .…”
Section: Talasemilerde Patogenez Hemoglobinunclassified